Chinese activity in the Balkans in the 21st century and its implications - Gibas-Krzak, Danuta (Balcanica Posnaniensia. Acta et studia, 2022)
Chinese activity in the Balkans in the 21st century and its implications. The paper aims to present how China’s multi-sectoral engagement in the Balkans is expressed as well as to show its significance for the development of this region. The Balkans are important for powerful players, due to their geopolitical and geostrategic location at the crossroads of communication routes between continents. China strongly influences the economic sphere of the countries on the Peninsula and uses the tools of public diplomacy to reduce the influence of other important players: the EU, Russia and the United States in the region. The author hypothesizes that China, like the United States at the end of the 20th century, tries to build a sphere of its influence on the Balkan Peninsula in the era of globalization. The Balkans could be the “gateway” to further Chinese expansion in Europe.